PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN DAN PERAN KUASA PENGGUNA ANGGARAN TERHADAP KINERJA PEMERINTAH DAERAH KABUPATEN KEPULAUAN TALAUD - Kasili, Sinthia Anelia; Saerang, David P. E (ACCOUNTABILITY, 2013)
This research aims to discover the effects of Participation in Budget Preparation and the Role of Authority of the Budget User on the Regional Government Performance. The research was conducted in the Talaud Regency, one of the Autonomy Regions in North Sulawesi. The samples were taken using purposive sampling. The research sample was the Authorized Officials of Budget Users in Satuan Kerja Perangkat Daerah Pemerintah Kabupaten Kepulauan Talaud which were as many as 103 people.The Multiple Linear Regression, descriptive statistics, classic assumption test, correlation coefficient  ( R) , determination coefficient  ( R² )  and hypothesis testing  ( t test and F test )  were used to analyze the data. This method of analysis used the Software Statistical Products and Solution Services  ( SPSS)  version 20.0.The results of the research shows that the Participation in Budget Preparation and the Role of Authority of the Budget User on the Regional Government Performance both partially and simultaneously. Therefore, the hypotheses proposed in the research were accepted.Key words : Participation in Budget Preparation, Role of Authority of the Budget User, Regional Government Performance.